Annual Report: Hawaiian Electric Industries Revenue down 19.6% Corporate Wire Date: 02 March 2016 04:34 EST (News Bites US - NYSE, 2016)
Income Statement Description USD Thousand USD Thousand Dec 31 2015 2014 Change % Revenues Electric utility 2,335,166 2,987,323 Down 21.8 Bank 267,733 252,497 Up 6.0 Other 83 -278 Recovery Total revenues 2,602,982 3,239,542 Down 19.6 Expenses Electric utility 2,061,050 2,711,555 Down 24.0 Bank 183,921 173,202 Up 6.2 Other 35,458 22,185 Up 59.8 Total expenses 2,280,429 2,906,942 Down 21.6 Operating income (loss) Electric utility 274,116 275,768 Down 0.6 Bank 83,812 79,295 Up 5.7 Other -35,375 -22,463 Deterioration 57.5 Total operating income 322,553 332,600 Down 3.0 Interest expense, net - other than on deposit liabilities and other bank borrowings 77,150 76,352 Up 1.0 Allowance for borrowed funds used during construction 2,457 2,579 Down 4.7 Allowance for equity funds used during construction 6,928 6,771 Up 2.3 Income before income taxes 254,788 265,598 Down 4.1 Income taxes 93,021 95,579 Down 2.7 Net income 161,767 170,019 Down 4.9 Preferred stock dividends of subsidiaries 1,890 1,890 Steady Net income for common stock 159,877 168,129 Down 4.9 Basic earnings per common share US$1.50 US$1.65 Down 9.1 Diluted earnings per common share US$1.50 US$1.63 Down 8.0 Dividends per common share 1.24 1.24 Steady Weighted-average number of common shares outstanding 106,418,000 101,968,000 Up 4.4 Net effect of potentially dilutive shares 303,000 969,000 Down 68.7 Adjusted weighted-average shares 106,721,000 102,937,000 Up 3.7 Balance Sheet Description USD Thousand USD Thousand Dec 31 2015 2014 Change % ASSETS Cash and cash equivalents 300,478 175,542 Up 71.2 Accounts receivable and unbilled revenues, net 242,766 313,696 Down 22.6 Available-for-sale investment securities, at fair value 820,648 550,394 Up 49.1 Stock in Federal Home Loan Bank, at cost 10,678 69,302 Down 84.6 Loans receivable held for investment, net 4,565,781 4,389,033 Up 4.0 Loans held for sale, at lower of cost or fair value 4,631 8,424 Down 45.0 Property, plant and equipment, net Land 90,890 94,093 Down 3.4 Plant and equipment 6,444,214 6,137,417 Up 5.0 Construction in progress 181,873 168,214 Up 8.1 6,716,977 6,399,724 Up 5.0 Less - accumulated depreciation -2,339,319 -2,250,950 Deterioration 3.9 4,377,658 4,148,774 Up 5.5 Regulatory assets 896,731 905,264 Down 0.9 Other 488,635 542,523 Down 9.9 Goodwill 82,190 82,190 Steady Total assets 11,790,196 11,185,142 Up 5.4 LIABILITIES AND SHAREHOLDERS' EQUITY Liabilities Accounts payable 138,523 186,425 Down 25.7 Interest and dividends payable 26,042 25,336 Up 2.8 Deposit liabilities 5,025,254 4,623,415 Up 8.7 Short-term borrowings-other than bank 103,063 118,972 Down 13.4 Other bank borrowings 328,582 290,656 Up 13.0 Long-term debt, net-other than bank 1,586,546 1,506,546 Up 5.3 Deferred income taxes 680,877 633,570 Up 7.5 Regulatory liabilities 371,543 344,849 Up 7.7 Contributions in aid of construction 506,087 466,432 Up 8.5 Defined benefit pension and other postretirement benefit plans liability 589,918 632,845 Down 6.8 Other 471,828 531,230 Down 11.2 Total liabilities 9,828,263 9,360,276 Up 5.0 Preferred stock of subsidiaries - not subject to mandatory redemption 34,293 34,293 Steady Commitments and contingencies Shareholders' equity Preferred stock, no par value, authorized 10,000,000 shares; issued: none Common stock, no par value, authorized 200,000,000 shares; issued and outstanding: 107,460,406 shares and 102,565,266 shares at December 31, 2015 and 2014, respectively 1,629,136 1,521,297 Up 7.1 Retained earnings 324,766 296,654 Up 9.5 Accumulated other comprehensive income (loss), net of taxes Net unrealized gains (losses) on securities -1,872 462 Deterioration Unrealized losses on derivatives -54 -289 Improved 81.3 Retirement benefit plans -24,336 -27,551 Improved 11.7 -26,262 -27,378 Improved 4.1 Total shareholders' equity 1,927,640 1,790,573 Up 7.7 Total liabilities and shareholders' equity 11,790,196 11,185,142 Up 5.4 Cash Flow Description USD Thousand USD Thousand Dec 31 2015 2014 Change % Cash flows from operating activities Net income 161,767 170,019 Down 4.9 Adjustments to reconcile net income to net cash provided by operating activities Depreciation of property, plant and equipment 183,966 172,762 Up 6.5 Other amortization 11,619 10,282 Up 13.0 Provision for loan losses 6,275 6,126 Up 2.4 Impairment of utility assets 6,021 1,866 Up 222.7 Other 1,672 758 Up 120.6 Loans receivable originated and purchased, held for sale -268,279 -155,755 Deterioration 72.2 Proceeds from sale of loans receivable, held for sale 275,296 155,030 Up 77.6 Gain on sale of credit card portfolio Increase in deferred income taxes 41,433 104,226 Down 60.2 Share-based compensation expense 6,542 9,287 Down 29.6 Excess tax benefits from share-based payment arrangements -978 -277 Deterioration 253.1 Allowance for equity funds used during construction -6,928 -6,771 Deterioration 2.\n